2
$\begingroup$

$$\int_{0}^{1} \frac{\ln(1+x)}{x} dx = \int_{0}^{1} \frac1x\cdot (x-x^2/2 + x^3/3 -x^4/4 \ldots)dx = \int_{0}^{1}(1 - x/2 + x^2/3 - x^4/4 \dots)dx = 1-\frac1{2^2} + \frac1{3^3} - \frac{1}{4^4} \dots = \frac{\pi^2}{12}$$

Also,

$$\int_{0}^{1} \frac{\ln(1-x)}{x}dx = -\int_{0}^{1}\frac1x \cdot (x+x^2/2 +x^3/3 \ldots)dx =- \int_{0}^{1}(1+x/2+x^2/3 \dots )dx = -( 1 + \frac1{2^2} + \frac1{3^3} \dots) = -\frac{\pi^2}{6}$$

Using these integral, I evaluate $$ \int_{0}^{1} \frac{\ln(x)}{1-x} $$

by letting $1-x=t$

$$ \int_{0}^{1} \frac{\ln(x)}{1-x} =\int_{0}^{1} \frac{\ln(1-t)}{t} dx = -\frac{\pi^2}{6}$$

However, I'm facing problem while integrating

$$\int_{0}^{1} \frac{\ln(x)}{1+x}$$ using the same above way.

$\endgroup$
1
  • $\begingroup$ The same trick of using the substitution $t=1-x$ won't work here, but one can expand in series though. $\endgroup$ Jun 10, 2018 at 8:53

3 Answers 3

5
$\begingroup$

Hint: integrate by parts.

Let $u = \ln(x)\implies u' = \dfrac1x$ and $v' = \dfrac1{1 + x}\implies v = \ln(1 + x)$. Therefore, $$\int\dfrac{\ln(x)}{1 + x}\,\mathrm dx = \ln(x)\ln(1 + x) - \int\dfrac{\ln(1 + x)}x\,\mathrm dx$$

$\endgroup$
2
  • $\begingroup$ Thank you. Can you tell me if the method I used to integrate the first two integrals is fine or not $\endgroup$
    – So Lo
    Jun 10, 2018 at 8:51
  • $\begingroup$ Yes, they seem fine. You can also verify using Wolfram Alpha. See this, this and this. $\endgroup$
    – an4s
    Jun 10, 2018 at 9:00
2
$\begingroup$

$$\int_0^1 x^m\ln x\,dx=\int_0^1 ye^{-(m+1)y}\,dy=-\frac1{(m+1)^2}.$$ Then $$\int_0^1\frac{\ln x}{1+x}\,dx=\sum_{m=0}^\infty(-1)^m \int_0^1 x^m\log x\,dx=\sum_{m=1}^\infty\frac{(-1)^{m+1}}{(m+1)^2} =-\frac{\pi^2}{12}.$$

$\endgroup$
0
$\begingroup$

Let,

$\begin{align}I&=\int_0^1 \frac{\ln x}{1-x}\,dx\\ J&=\int_0^1 \frac{\ln x}{1+x}\,dx\\ \end{align}$

$\begin{align}I-J&=\int_0^1 \frac{2x\ln x}{1-x^2}\,dx\end{align}$

Perform the change of variable $y=x^2$,

$\begin{align}I-J&=\frac{1}{2}\int_0^1 \frac{\ln x}{1-x}\,dx\\ &=\frac{1}{2}I\end{align}$

Therefore,

$J=\dfrac{1}{2}I$

If $I=-\dfrac{\pi^2}{6}$ then $J=-\dfrac{\pi^2}{12}$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.